Alltech FEI World Equestrian Games. Issue 1 (4th January 2016) - Medcalfe, Simon; Frentzel, Caroliegh
Abstract : Synopsis: This case requires students to analyze the economic impact of a sporting mega-event. Mega-events are defined as infrequent events (maybe spread over several days) that attract a large crowd of visitors. Economic impact studies are becoming ubiquitous in analyzing the impact of sporting events, universities and other businesses. Properly constructed these reports can be valuable tools for decision makers. Unfortunately, many impact studies are not constructed accurately and may mislead and misrepresent information. This case raises these issues so that students may be better placed to critically analyze the impact of mega-events. Research methodology: There are a number of academic articles that have analyzed these types of events and they are referred to in this case and instructor's manual. The academic articles are complemented by one of the author's firsthand knowledge of the event through working at the World Equestrian Games, a third-party economic impact study and media reports. Relevant courses and levels: The case would be appropriate for a variety of undergraduate courses including upper-level economics (particularly regional economics or local economic development), marketing, sport management as well as some finance courses such as public finance. Outside of business courses, it would be well suited to a course in political economy or public policy. The case could potentially be used in a graduate course in sports management or a course in local economic development (in an MBA or MPA program).